Synthesis of Tercopolymer Derived from Maleic Anhydride, Vinyl Acetate and Acrylamide - PANDEY, A.K.; KUMAR, D.; SINGH, S.P.; SINGH, L. (Asian Journal of Chemistry, 2010)
The tercopolymer of maleic anhydride, vinyl acetate and acrylamide was prepared under different temperature conditions using metal complex as initiator. The tercopolymer, thus formed was characterized by FTIR and its thermal degradation by TGA. It will be worth finding to ensure the optimum temperature at which the tercopolymer synthesized reports maximum yield.